Native title in australia: An ethnographic perspective - Sutton, Peter (New York Cambridge University Press, 2010)
Peter Sutton highlights fundamental anthropological issues concerned with customary rights, kinship, identity and spirituality that are highly relevant to land claim cases. Native land claims continue to be one of the most controversial political, legal and moral issues in contemporary Australia. Ever since the High Court's Mabo decision of 1992, the attempt to understand and adapt "native title" to different contexts and claims has been an ongoing concern for all involved.